Animal DNA and halal status of chocolate products in Malaysia - Mohd Borhanuddin, Zakaria; Mohd Izhar Ariff, Mohd Kashim; Ahmad Yunus, Mohd Noor (2020)
Chocolate is a type of confectionary product loved by most of the Muslim society in Malaysia. Various types of biscuits, cakes and desserts may be produced with chocolate as an ingredient. Thus, chocolate products are encouraged by the Halal Council of Malaysia for an authentic halal certification. This led to tension after a report went viral in local newspapers that pig DNA was found on a well-known brand of chocolate in Malaysia. Muslims were shocked when the chocolate involved had the halal certified logo from the Department of Islamic Development of Malaysia (JAKIM). The consequence was that Muslims tend to boycott the particular chocolate brand. Therefore, the purpose of this paper was to identify the ingredients used in making chocolate and the method of determining its legal status. The definition of DNA and and how it can contaminate to other substances were highlighted and discussed. A qualitative case study design is conducted on chocolate making using a content analysis of primary sources of Islamic studies and sciences such as al-Quran, hadith, contemporary fiqh, science books and journals. Results indicated that the method of detecting animal DNA in chocolate was through Polymerase Chain Reaction (PCR) where pig DNA is detected with primers 5’- GCCTAAATCTCCCCTCAATGGTA-3’ and (reverse) 5’ -ATGAAAGAGGCAA ATAGATTTTCG-3’. Pig traces can contaminate other food products either deliberately or unintentionally. Legal ruling was that, it is haram (prohibited) if pig DNA was placed intentionally by human intervention or negligence. However, unintentionally contamination by human is affirmed as halal (permissible) based on the general rule by the mukalaf (authority).